The URGENCY OF THE VALUES OF RELIGIOUS MODERATION IN P5 AND PPRA AT RA - dwi hasibuan; Imamah Imamah; Rahayuliana Rahayuliana; Kartika Nurwita Kurniati Kurniati; Mu’awannah Mu’awannah; Sri Ratna (International Conferences on Early Childhood Education Proceedings, 2023)
The title of the research is the urgency of the value of religious moderation in the project to strengthen the Pancasila student profile and Rahmatan lil 'Alamiin (P5 and PPRA) student profiles in Raudhatul athfal (RA). Raudhatul Athfal is the stage of formal education for early childhood with Islamic characteristics with age of 4 to 6 years, this range is also known as the golden age, so it is a very appropriate time to stimulate all aspects of child development, children is exploring new things that he encounters, so this is the right time to embed national character and religious moderation from an early age. Religious moderation is a way of looking at, responding to and practicing religious practices in public life by carrying out religious teachings that protect human rights and prioritize the common good based on the principles of justice, proportionateness and compliance with state law. The implementation of religious moderation in RA is packaged in a project frame known as P5 and PPRA. This research began in March to May, using qualitative methods and a literature review approach. The results of the study state that the value of religious moderation needs to be instilled from an early age through P5 and PPRA